2020
DOI: 10.1017/s0029665120007892
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-dense protein as a primary dietary strategy in healthy ageing: please sir, may we have more?

Abstract: A progressive decrement in muscle mass and muscle function, sarcopoenia, accompanies ageing. The loss of skeletal muscle mass and function is the main feature of sarcopoenia. Preventing the loss of muscle mass is relevant since sarcopoenia can have a significant impact on mobility and the quality of life of older people. Dietary protein and physical activity have an essential role in slowing muscle mass loss and helping to maintain muscle function. However, the current recommendations for daily protein ingesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 149 publications
(278 reference statements)
0
9
0
Order By: Relevance
“…Most of the selected studies in this meta‐analysis (65 out of 74) provided animal protein to their subjects. Therefore, our findings reflect mainly the effect of animal‐based protein sources 11 . Approximately a quarter of the selected studies showed an increased risk of bias due to poor blinding during the study or the data analysis ( Figures S1 and S2).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Most of the selected studies in this meta‐analysis (65 out of 74) provided animal protein to their subjects. Therefore, our findings reflect mainly the effect of animal‐based protein sources 11 . Approximately a quarter of the selected studies showed an increased risk of bias due to poor blinding during the study or the data analysis ( Figures S1 and S2).…”
Section: Discussionmentioning
confidence: 83%
“…Nonetheless, many questions still arise when constructing dietary or physical activity guidelines focusing on skeletal muscle health 10 . Particularly, the optimal daily protein intake level required to optimize skeletal muscle mass gain or maintenance in healthy adults, which is still largely unclear 10–13 . It is also unclear whether additional protein ingestion can preserve lean body mass and muscle function in healthy adults who do not engage in RE 14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Overweight individuals, such as those prominent in this study, have excessive caloric intake, but intake may be deficient in certain macronutrients (eg, protein) or micronutrients (eg, vitamin D, calcium, magnesium). [10][11][12][13] Overnutrition can result from poor food choices, limited access to healthy foods, energy imbalance related to low physical activity, and/or to genetic predisposition to certain metabolic abnormalities. 14,15 Overnutrition and obesity are both risk factors for the development of chronic conditions such as type 2 diabetes mellitus, metabolic syndrome, atherosclerosis, and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%